1986
DOI: 10.1177/001872678603901106
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Inequity, Satisfaction, and Conflict in Task-Oriented Groups

Abstract: The study reported here was descriptive in nature and looked at 375 subjects involved in a group task. The research focus was on individual satisfaction, type, and amount of conflict, its resolution, perceived inequity, and quality of outcome. The results indicated that greater inequity was associated with people conflicts, which in turn were managed primarily with avoidance tactics. Task conflicts were managed mainly with integrative styles. Greater satisfaction was associated with integrative tactics. Percep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
90
0
7

Year Published

1994
1994
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(101 citation statements)
references
References 22 publications
4
90
0
7
Order By: Relevance
“…The main objective was to solve conflict in the sense of reducing its amount, instead of attempting to manage it, which does not necessarily imply such a reduction [14]. Such an approach to conflict originated from the use of negative value-laden definitions of conflict, which led to the assumption that the latter has only destructive effects and should therefore be avoided altogether.…”
Section: Dispute Resolutionmentioning
confidence: 99%
“…The main objective was to solve conflict in the sense of reducing its amount, instead of attempting to manage it, which does not necessarily imply such a reduction [14]. Such an approach to conflict originated from the use of negative value-laden definitions of conflict, which led to the assumption that the latter has only destructive effects and should therefore be avoided altogether.…”
Section: Dispute Resolutionmentioning
confidence: 99%
“…Although conflict in teams and organizations is virtually unavoidable (Jehn, 1995), scholars have found conflict to be both harmful and beneficial to team performance (Troth, 2009). For example, conflict may cause reduced productivity and satisfaction in teams (Wall & Nolan, 1986), studies by Chatman (2000) showed that organizations, where functional conflict is part of the culture within teams, can improve decision quality as different ideas are expressed and resolved openly (Jehn and Chatman, 2000). Team conflict is multidimensional, consisting of both relationship-and task-based elements (Jehn & Bendersky, 2003;Korsgaard et al, 2008).…”
Section: Task Conflict In Teamsmentioning
confidence: 99%
“…In defining the concept of the conflict, many scholars believe, that the nature of conflict is related to ethnicity, cross cultural disputes, religious differences and socio economic inequality (Balkenohl 1971;Mitroff, Emshaff 1979;Wall, Nolan 1986;Litterer 1996;Robbins 1998;Bennett 2002;Jehn, Bendersky 2003;Fial et al 2009). Fenn et al (1997 compared conflict to a disease -it exists if there is a conflict between the interests, regardless of whether there is a claim or not.…”
Section: Literature Reviewmentioning
confidence: 99%